Voluntary childlessness and Islamic perspectives: a systematic literature review - Duasa, Jarita; Zulkifli, Izyani; Idris, Zera Zuryana (Universiti Sultan Zainal Abidin, 2025)
Voluntary childlessness- defined as the deliberate choice by individuals or couples to remain childfree - poses theological, legal, ethical, and socio-cultural questions within Islamic contexts. Despite the growing prevalence of childfree decisions in Muslim societies, scholarly inquiry remains limited, fragmented, and regionally concentrated. This study conducts a systematic literature review (SLR) of 45 academic publications, synthesizing the discourse through five analytical themes: (1) theological and ethical frameworks, (2) legal and jurisprudential perspectives (fiqh), (3) gender and societal expectations, (4) modernity, individualism, and cultural change, and (5) bioethical and policy implications. Findings indicate that while Islamic theology and jurisprudence traditionally valorize procreation, there is historical precedent and contemporary discourse supporting limited reproductive autonomy, including contraception. However, voluntary, permanent childlessness remains a contested domain, with strong gendered stigma and insufficient fatwa engagement. The review reveals methodological gaps, a dominance of Southeast Asian case studies, and limited engagement with the maqasid al-shariah framework - particularly hifz al-nasl (preservation of lineage). This paper identifies a critical need for interdisciplinary, comparative, and jurisprudentially diverse research that acknowledges the lived experiences and spiritual reasoning of voluntarily childfree Muslims. Recommendations for future studies include qualitative ethnographies, comparative fiqh analysis, and gender-focused policy inquiry to broaden the Islamic bioethical discourse on reproductive autonomy